Investigating Klebsiella pneumoniae biofilm preservation for scanning electron microscopy. Issue 2 (3rd February 2023) - Fleeman, Renee M.; Mikesh, Michelle; Davies, Bryan W.
Abstract : Klebsiella pneumoniae biofilm formation is associated with chronic and relapsing infections. Scanning electron microscopy (SEM) is a powerful tool for characterizing biofilm structure and studying their formation. Reliable visualization of biofilm structure requires careful sample preservation, otherwise there may be loss of non-covalent interactions that are susceptible to damage during the dehydration and washing preparation steps. However, no standard procedure has been adopted in the literature to fix K. pneumoniae biofilm for scanning electron microscopy studies. This lack of standardization makes it challenging to compare results between studies and determine the degree to which native structures have been preserved. To advance this critical area of study, we investigated different scanning electron microscopy fixation methods for K. pneumoniae biofilm preservation. Our study reveals the impact preparation steps can have on retaining in biofilm architecture observed using scanning electron microscopy. Using fixation methods developed through our studies, we show that although species that overproduce capsular extracellular polysaccharides produced more robust biofilms, K. pneumoniae can form a developed biofilm in the absence of capsular polysaccharides.